Electoral laws as political consequences: Explaining the origins and change of electoral institutions - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2007)
In this review article, I identify the key questions raised by the treatment of electoral systems not as causal influences on party systems but as effects or byproducts of party systems. Framing these questions in the context of the classic consequences-oriented study of electoral institutions, I first review the classic approach, which treats electoral systems as causes, and explore the potential implications when electoral systems are viewed instead as outcomes of party systems. I then survey a variety of principal explanations of the origins and change of electoral laws, followed by a focus on several of the more explicitly defined models of this process. I conclude by discussing—and contesting—the notion that except for exceptional founding episodes of institutional choice, electoral systems eventually stabilize as equilibrium institutions.